(untitled) (Research, Society and Development, 2022)
The present work presents an investigation about the constitution of a rural education school with the objective of rescuing the constitution of the rural school, in the context of the organization of the MST and its struggles and relevant pedagogical principles to be considered in the pedagogical action of rural schools. Its motivation is the systematization of details on this theme, whose procedure was the collection of data with residents in the neighborhood of the Antônio Conselheiro school in Santana do Livramento. Based on these reports, we sought to obtain an insight into the lived experiences of each subject and to recognize the importance of the MST social movement’s role in these struggles with the consequences of the results that were obtained from them. According to the data analysis carried out, the results demonstrate the importance of the constitution of this rural school for the region. Finally, the work explains the MST’s contributions to the debate on education; after all, it is the social movements that express the contradictions of our society and the social movements that are the expression of the future, the fertile base for an education that distances itself from the capitalist and bourgeois perspective.